DETERMINANTS OF BUDGET DEFICITS: THE EFFECTS OF THE COVID-19 CRISIS - Tevdovski, Dragan; Jolakoski, Petar; Stojkoski, Viktor (Economic Annals, 2022)
This paper revisits the discussion on the determinants of budget balances and investigates the change in their effect in the context of the COVID-19 crisis. The analysis uses data on 43 countries and a system generalised method of moments approach. The results show that the overall impact of the global pandemic has led to a disproportionate increase in the estimated effects of the macroeconomic determinants on the budget balance. We also find that more developed economies were able to implement higher stimulus packages for the same relative level of primary balance. We believe that one of the factors affecting this outcome is that more of their government debt is held in domestic currency.